Targeting cell death mechanisms: the potential of autophagy and ferroptosis in hepatocellular carcinoma therapy - Liu, Beibei; Liu, Ling; Liu, Yang (Frontiers in Immunology, 2024)
Ferroptosis is a type of cell death that plays a remarkable role in the growth and advancement of malignancies including hepatocellular carcinoma (HCC). Non-coding RNAs (ncRNAs) have a considerable impact on HCC by functioning as either oncogenes or suppressors. Recent research has demonstrated that non-coding RNAs (ncRNAs) have the ability to control ferroptosis in HCC cells, hence impacting the advancement of tumors and the resistance of these cells to drugs. Autophagy is a mechanism that is conserved throughout evolution and plays a role in maintaining balance in the body under normal settings. Nevertheless, the occurrence of dysregulation of autophagy is evident in the progression of various human disorders, specifically cancer. Autophagy plays dual roles in cancer, potentially influencing both cell survival and cell death. HCC is a prevalent kind of liver cancer, and genetic mutations and changes in molecular pathways might worsen its advancement. The role of autophagy in HCC is a subject of debate, as it has the capacity to both repress and promote tumor growth.Autophagy activation can impact apoptosis, control proliferation and glucose metabolism, and facilitate tumor spread through EMT. Inhibiting autophagy can hinder the growth and spread of HCC and enhance the ability of tumor cells to respond to treatment. Autophagy in HCC is regulated by several signaling pathways, such as STAT3, Wnt, miRNAs, lncRNAs, and circRNAs. Utilizing anticancer drugs to target autophagy may have advantageous implications for the efficacy of cancer treatment.